2006
DOI: 10.1105/tpc.106.046417
|View full text |Cite
|
Sign up to set email alerts
|

The CauliflowerOrGene Encodes a DnaJ Cysteine-Rich Domain-Containing Protein That Mediates High Levels of β-Carotene Accumulation

Abstract: Despite recent progress in our understanding of carotenogenesis in plants, the mechanisms that govern overall carotenoid accumulation remain largely unknown. The Orange (Or) gene mutation in cauliflower (Brassica oleracea var botrytis) confers the accumulation of high levels of β-carotene in various tissues normally devoid of carotenoids. Using positional cloning, we isolated the gene representing Or and verified it by functional complementation in wild-type cauliflower. Or encodes a plastid-associated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
430
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(453 citation statements)
references
References 71 publications
(81 reference statements)
9
430
0
6
Order By: Relevance
“…DnaJ proteins are molecular chaperones that specifically regulate DnaK-like proteins involved in protein folding. Hsp70s, DnaK homologs in chloroplasts, play an important role in a number of processes (Liu et al, 2005;Lu et al, 2006). However, CYO1 lacks the J domain responsible for stimulating DnaK ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DnaJ proteins are molecular chaperones that specifically regulate DnaK-like proteins involved in protein folding. Hsp70s, DnaK homologs in chloroplasts, play an important role in a number of processes (Liu et al, 2005;Lu et al, 2006). However, CYO1 lacks the J domain responsible for stimulating DnaK ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Or is involved in the differentiation of noncolored plastids into chromoplasts for carotenoid accumulation (Lu et al, 2006). BSD2 is required for posttranslational regulation of the L subunit of ribulose-1,5-bis-phosphate carboxylase/oxygenase (Rubisco) (Brutnell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Or gene has been introduced into the potato cultivar Desiree where expression of the Or transgene in tubers of transgenic lines led to increased levels of violaxanthin, lutein, and β-carotene. Their total carotenoid level was approximately six-fold higher than in the non-transformed or vector-only controls 43 .…”
Section: Carotenoid Biosynthesismentioning
confidence: 74%
“…The Y gene has been mapped to chromosome 3 by Bonierbale et al 42 . Recently, Lu et al 43 demonstrated that the Or gene mutation in cauliflower induces differentiation of β-carotene-containing chromoplasts in non-pigmented curd tissue. Chromoplasts are carotenoid-accumulating plastids found in many fruits and flowers, whereas the Or gene is a dominant mutation that confers orange pigmentation to the normally unpigmented curd and apical meristem of cauliflower.…”
Section: Carotenoid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation